PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA DENGAN MODEL PEMBELAJARAN STAD BERBANTUAN ALAT PERAGA JAM SUDUT - Della Amelia; Yusnira; Astuti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One of he essential aspects of learning mathematics is concept udestanding. Students need to understand the basic concepts of mathematics well. Concept of understand ability is often an obstacle or same student so innovative learning approaches ae needed to help students overcome these obstacles. The mathematical conceptual understanding ability of fifth-grade students at UPT SDN 019 Muara Uwai is still relatively low. This can be seen from the learning outcomes, which show that most students have not yet mastered mathematical concepts thoroughly. The low level of conceptual understanding affects students’ overall learning achievements. This study aims to improve the mathematical conceptual understanding ability of fifth-grade students at UPT SDN 019 Muara Uwai by implementing an appropriate learning approach. This research is a Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of two meetings. The subjects of this study were all fifth-grade students, totaling 15 students. Data collection techniques used in this study included interviews, observations, documentation, and tests. The collected data were analyzed using both qualitative and quantitative methods. Based on the research results, in the first meeting of Cycle I, only 9 students (60%) achieved the minimum mastery criteria with an average score of 68. In the second meeting of Cycle I, the number of students who met the criteria increased to 11 students (73,33%) with an average score of 76. In the first meeting of Cycle II, 13 students (86,67%) achieved mastery with an average score of 80. This increased further in the second meeting of Cycle II to 14 students (93,3%) with an average score of 85. Based on these results,it can be concluded that application of the STAD learning model wih the help of the corner clock can improve the concept understanding ability of fifth-grade students of Muara Uwai 019.